Cholelithiasis in a neonate with chylous ascites. - Siahanidou, T; Mikou, C; Karra, P; Pappas, D; Zellos, A; Mandyla, H (J Perinatol, 2010)
A case of a neonate with congenital chylous ascites resulting from primary lymphatic dysplasia is described. The baby also presented with a sludge ball in the gallbladder that eventually progressed to gallstones. The association of chylous ascites with cholelithiasis in this neonate is discussed.
Keywords: Cholagogues and Choleretics; Cholelithiasis; Chylous Ascites; Humans; Infant; Lymphatic Abnormalities; Male; Newborn; Prenatal; Ultrasonography; Ursodeoxycholic Acid